Antenatal telephone support intervention and uterine artery Doppler screening: A qualitative exploration of women׳s views. Issue 5 (May 2015) - Snaith, Vikki J.; Robson, Stephen C.; Hewison, Jenny
Abstract: Objectives: to gain insight into low risk nulliparous women׳s experiences of a telephone support intervention (TSI) and TSI with uterine artery Doppler screening (UADS) intervention and their views of the structure of current antenatal care provision. Design: postnatal semi-structured interviews were analysed using a thematic framework approach. The interviews formed a subset of data from a mixed methods study. Setting and participants: participants were 45 low risk nulliparous women who had consented to take part in a randomised controlled trial of two antenatal support interventions; the trial was conducted at a large maternity unit in the North East of England, UK from 2004 to 2007. Findings: most of the women in the study expressed positive views about the telephone support intervention (TSI) and the antenatal care they had received. Uterine artery Doppler screening was acceptable to women but did not feature highly when women recalled their antenatal experiences. Those who viewed their pregnancy as complicated by medical, social or emotional difficulties would have preferred more frequent antenatal visits. Views of antenatal care provision were influenced by women׳s perception of their pregnancy progression and the relationship developed with their midwife. Key conclusions and implications for practice: although the TSI was viewed positively by women, it was valued most by those who required additional support. The intervention was not a substitute for face to face midwifery visits. Future research is needed to investigate the potential of utilising telephone contact to provide antenatal care for women who have pregnancies complicated by physical, psychological or emotional issues. The findings were consistent with previous evidence to show that the relationship between women and midwives is fundamental to women׳s experience of antenatal care. Highlights: The interventions were not a substitute for face-to-face contacts. Telephone support is particularly valued by women who require additional support. Women who have concerns during pregnancy prefer more antenatal visits. Uterine artery Doppler screening is acceptable to women. The relationship between a woman and her midwife is a fundamental aspect of effective care.